1988
DOI: 10.1002/ijc.2910410623
|View full text |Cite
|
Sign up to set email alerts
|

Absence, or low expression, of leukocyte adhesion molecules CDI1 and CD18 on burkjtt lymphoma cells

Abstract: Leukocyte adhesion to cells is mediated by the cell-surface glycoprotein complex CD11a-c/CD18 and, in some cases, the glycoprotein gp84. The process is associated with leukocyte activation and modulates lymphocyte proliferation and maturation. Epstein-Barr virus (EBV)-transformed normal B lymphocytes give rise to lymphoblastoid cell lines (LCLs) which grow as large clusters mediated by adhesion molecules. In contrast, newly explanted EBV-infected Burkitt lymphoma (BL) cells usually grow as single cells or as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…We found that the level of expression of class-I MHC antigens detected using the W6i32 MAb, which recognizes a monomorphic HLA A, B, C determinant, was significantly lower (p < 0.05) in Burkitt cells with t(8;14) than in lymphoblastoid cells. Decreased expression of class-I MHC antigens has also been reported recently in other Burkitt cells using the same antibody W6/32 (Patarroyo et al, 1988) and a panel of MAbs directed against several polymorphic HLA class-I determinants (Torsteinsdottir et al, 1988), although previous reports indicated that there was no difference in class-I MHC antigen expression between other Burkitt and lymphoblastoid cell lines using the W6/32 MAb (Rooney et al, 1984Masucci et al, 1987). We also found a significant correlation (r = 0.70, p < 0.05) between the expression of insulin receptors and class-I MHC antigens when data for both lymphoblastoid and Burkitt cells were combined (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…We found that the level of expression of class-I MHC antigens detected using the W6i32 MAb, which recognizes a monomorphic HLA A, B, C determinant, was significantly lower (p < 0.05) in Burkitt cells with t(8;14) than in lymphoblastoid cells. Decreased expression of class-I MHC antigens has also been reported recently in other Burkitt cells using the same antibody W6/32 (Patarroyo et al, 1988) and a panel of MAbs directed against several polymorphic HLA class-I determinants (Torsteinsdottir et al, 1988), although previous reports indicated that there was no difference in class-I MHC antigen expression between other Burkitt and lymphoblastoid cell lines using the W6/32 MAb (Rooney et al, 1984Masucci et al, 1987). We also found a significant correlation (r = 0.70, p < 0.05) between the expression of insulin receptors and class-I MHC antigens when data for both lymphoblastoid and Burkitt cells were combined (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…MW markers as in Figure 2. expression is also seen in Burkitt's lymphomas (Patarroyo et al, 1988). CD23, a B-cell-activation antigen, usually expressed by LCL but not BL , was also demonstrated on most of the monkey lymphomas.…”
Section: Discussionmentioning
confidence: 92%
“…In view of the evidence that lymphoblastoid cell lines expressing high levels of IL-6 are more tumorigenic than control lines, it was of interest to know whether these lines might display a w Burkitt's lymphoma-like phenotype (37)(38)(39)(40)(41)(42)(43). However, all :25,6M lymphoblastoid cell lines, regardless of how much IL-6 they nt produced and how tumorigenic they were, expressed similar levels of the B cell activation antigen CD23, and the cell adhe- Given that IL-6 promotes the proliferation ofEBV-immortalized cells (16)(17)(18), the tumorigenic effect of IL-6 could depend upon IL-6 providing a growth advantage to EBV-immor- tch Ed much of this bioactivity derived from murine IL-6 in the culture supernatant, because it was largely neutralized by a heteroantiserum to mouse IL-6 (28) and only to a small degree by a MAb to human IL-6 (29).…”
Section: Resultsmentioning
confidence: 99%